Quality of Life in Patients with Knee Osteoarthritis: Quality of Life in Patients with Knee Osteoarthritis - Asif , Tania; Ali Rana, Arif; Ahmed Zahoor, Idrees; Ghaffar, Noman; Ahmad, Irfan; Idrees, Qasim (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Osteoarthritis is a joint degenerative disease. Old age is the usual cause of knee osteoarthritis. Knee osteoarthritis affects quality of life (physical, social and psychological) of patient and can cause other health related problems. Most people who undergo knee osteoarthritis have serious consequences, which affect their quality of life. Objective: The purpose of this study was to evaluate the quality of life in patient by knee osteoarthritis. Methods: This was a cross sectional study that was conducted in Lahore, Pakistan in 2017. The sample size of 192 was taken with the age range of 30 to 70 years. SF-36 V2 extracted questionnaire was used to find out the quality of life in patients by knee osteoarthritis. People were asked about the effect of knee osteoarthritis on their physical, social and psychological health and result was calculated. Results: Quality of life was seen in 192 individuals having knee osteoarthritis with mean age of 47.66 years (range from 30 to 70). A strong impact of osteoarthritis was found on quality of life of such patients. Physical health limitation was found to be 59.9% and psychological impact was 49.5%. Conclusion: It was concluded that people with knee osteoarthritis had poor quality of life. Their physical, social and psychological health was compromised to a healthy individual.